Dilution of Earnings per Share in an Option Pricing Framework. - Vigeland, Robert L. (The Accounting Review, 1982)
ABSTRACT: The currently prescribed method of dealing with potentially dilutive securities in earnings per share calculations is reconsidered in light of the more recent development of equilibrium pricing models for options and convertible securities. This new treatment of an old problem offers a theoretical structure founded upon recent developments in finance. It is shown that fairly precise statements about the timing of voluntary conversion or exercise of potentially dilutive securities are often possible. Moreover, assessments of the probabilities of future stock prices reaching levels which would allow conversion or exercise can be derived from a widely used stochastic model of security price behavior. Some implications for policy are discussed.